2021
DOI: 10.1002/hsr2.287
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors associated with high‐flow nasal cannula success for COVID‐19‐related acute hypoxemic respiratory failure

Abstract: During the coronavirus disease 2019 (COVID-19) pandemic, oxygen support management for critically ill patients with acute hypoxemic respiratory failure (AHRF) was a key component of clinical decisionmaking. 1 There is a lack of knowledge regarding the use of high-flow nasal cannula (HFNC) in COVID-19 patients with AHRF. Most hospitals adopted an early-intubation strategy leading to a high intubation rate and the demand for intensive care unit (ICU)-beds overwhelmed hospital resources. With a low ICU bed-to-pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 12 publications
1
23
1
2
Order By: Relevance
“…The observed difference is probably owing to the discrepancy in clinical characteristics of treated patients, primarily the severity of the disease. Namely, the ROX index at the time of hospital admission, a valuable indicator of poor outcomes in patients with AHRF, was substantially lower in our and Hu’s study in comparison to the studies with lower mortality rates [ 32 , 33 , 40 , 41 , 42 ]. Furthermore, during the time in which the study was conducted, the British variant of SARS-CoV-2 breached our department, thus yielding less favorable outcomes.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…The observed difference is probably owing to the discrepancy in clinical characteristics of treated patients, primarily the severity of the disease. Namely, the ROX index at the time of hospital admission, a valuable indicator of poor outcomes in patients with AHRF, was substantially lower in our and Hu’s study in comparison to the studies with lower mortality rates [ 32 , 33 , 40 , 41 , 42 ]. Furthermore, during the time in which the study was conducted, the British variant of SARS-CoV-2 breached our department, thus yielding less favorable outcomes.…”
Section: Discussioncontrasting
confidence: 71%
“…In terms of mortality, our cohort of patients in which HFNO failed yielded similar results as the aforementioned study by Hu et al [ 32 ]. However, other studies reported much lower mortality rates among their patients [ 31 , 34 , 40 ]. The observed difference is probably owing to the discrepancy in clinical characteristics of treated patients, primarily the severity of the disease.…”
Section: Discussionmentioning
confidence: 92%
“…After excluding duplicates and evaluating the full texts of articles, we identified 25 eligible studies (1 RCT, 12 case-control studies, and 12 cohort studies). 14 38 The search and screening process is described in Figure 1 . The main characteristics of the articles included in the meta-analysis are shown in Tables 1 , 2 , 3 and 4 .…”
Section: Resultsmentioning
confidence: 99%
“…A total of 586 out of 2055 patients on HFNC from 20 studies 14 , 16 24 , 26 28 , 30 , 33 38 ultimately died, for a mortality rate of 0.23 (95% CI: 0.19–0.29, I 2 = 88%; Figure 3 (b) ) . A total of 529 out of 1124 patients from 14 studies 14 , 16 18 , 20 , 23 , 24 , 26 , 29 , 30 , 33 , 35 , 36 , 38 experienced HFNC failure (escalation to NIV or intubation and/or death), for a failure rate of 0.47 (95% CI: 0.42–0.51, I 2 = 56%; Figure 3 (c) ) . When reported, the ROX index after the initiation of HFNC was 5.0 ± 2.4, the duration of HFNC was 4.9 ± 5.0 days, and the length of the hospital stay was 19.6 ± 13.6 days.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the use of HFNCO led to a decrease in intubation rate and did not increase mortality 3,5–7 . Some studies found a decrease in the length of stay and a decrease in mortality for patients treated with HFNCO 6,8 . However, the use of HFNCO on patients not infected with SARS‐CoV‐2 and presenting acute respiratory failure is associated with greater mortality when HFNCO fails within 48 h after its initiation.…”
Section: Introductionmentioning
confidence: 99%